The Effect of Financial Literacy on MSME Performance Through Financial Access and Financial Risk Attitude as a Mediation Variable - Anisa Salsabila Kemala Fikri; Katiya Nahda (Jurnal Economic Resource, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in increasing the rate of economic growth in developing countries, especially Indonesia. The purpose of this study is to test the variable that evaluates the performance of SMEs, namely the financial literacy of the organizers. Equipped with the median variable, namely access to financial facilities and financial risk tolerance. Through a quantitative approach and SEM data analysis. The sample numbered 165 respondents managing MSMEs in the Yogyakarta City area because they contributed a lot to the MSME sector in Indonesia. This study found a positive impact on financial literacy, access to finance and financial risk attitudes on the performance of MSMEs. It was also found that the mediating role of financial access and financial risk attitudes was related to the relationship between literacy and performance.